2020
DOI: 10.1108/heswbl-09-2019-0111
|View full text |Cite
|
Sign up to set email alerts
|

Skills in European higher education mobility programmes: outlining a conceptual framework

Abstract: PurposeCredit mobility has been acknowledged not only to broaden personal and intellectual horizons but also to have positive effects on the skills development and employability of undergraduate students. Academics, policymakers and organizations representing the labour market have presented a broad number of skills-related explorations proposing different frameworks to help develop students' skills. However, the identification of explicit skills is still a difficult endeavour. This study aims to revise main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Organizations and stakeholders at all levels are committed to developing frameworks and undertaking research to better understand the new professional skills that are required (Garcia-Esteban and Jahnke, 2020) in the IT job market (Kurbanov et al, 2020). The professional profile is being transformed in the field of IT, and this transformation is mainly characterized by the new skills and qualifications that an employee has to develop.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations and stakeholders at all levels are committed to developing frameworks and undertaking research to better understand the new professional skills that are required (Garcia-Esteban and Jahnke, 2020) in the IT job market (Kurbanov et al, 2020). The professional profile is being transformed in the field of IT, and this transformation is mainly characterized by the new skills and qualifications that an employee has to develop.…”
mentioning
confidence: 99%
“…Recent literature has assessed the critical skills required for the new technological and digital paradigm and assumes that graduates will need to develop strong social skills, including communication, creativity, critical thinking and ethical values (Garcia-Esteban and Jahnke, 2020). Although technology advances require technical skills in employees, several studies highlight the role of cognitive skills, or the so-called “soft skills,” in improving the professional profile of a worker (Garcia-Esteban and Jahnke, 2020). Nonetheless, students do not have clear and convergent information on what the job market expects, resulting in underdevelopment of the appropriate skills, as well as misguidance in their professional choices.…”
mentioning
confidence: 99%
“…In other words, no common taxonomy is used to organize various competencies in a standardized manner. Nevertheless, it was observed that academia, international organizations, and public policy managers in government are beginning to focus on key basic competencies that are global and, therefore, transferable [24,40]. Studies that analyzed competencies required in the labor field projected cognitive and learning abilities, yet programs that involve mobility become attractive when considering employability, management, and career development such as life skills [24].…”
Section: Resultsmentioning
confidence: 99%
“…In the same manner, pointing out that the sum of the percentages presented in Figure 4 is 97.87% is important because the remaining 2.13% is associated with studies that were conducted on students (the sample of studies corresponds to managers and administrative personnel, among others). [23,24] and deployed according to academic level where the studies were conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation